Perbandingan Metode Economic Order Quantity (EOQ) Dan Just In Time (JIT) Terhadap Pengendalian Persediaan Bahan Baku - Budi Utami; Eny Setyariningsih (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2019)
The management and control of raw material inventories is an activity commonly found in industrial and manufacturing companies. There are two methods of controlling inventory, namely Economic Order Quantity (EOQ) and Just In Time (JIT). In determining inventory, companies tend to calculate it in the form of forecasting. Inventories that are too large will add to the cost of ordering (ordering cost) and storage costs (carring cost). Conversely, a small amount of inventory will reduce company profits due to lost opportunity for profit (opportunity cost) and incur back order costs (back order cost). Therefore it is important for companies to carry out inventory control which will affect the efficiency of inventory costs. This type of research is a comparative study comparing the Economic Order Quantity (EOQ) method with the Just In Time (JIT) method to the efficiency of inventory costs in Pateh SMEs. The results of the comparison. From the results of the analysis and calculations that have been carried out it is known that the Just In Time (JIT) control method is more appropriate to be applied to the "PATEH" home industry because the total inventory costs are smaller than the total inventory costs of the Economic Order Quantity (EOQ) method.